PENGARUH KEPEMIMPINAN, MOTIVASI KERJA DAN KOMPENSASI FINANSIAL TERHADAP KINERJA KARYAWAN PT. LUTVINDO WIJAYA PERKASA - Setianingsih, Rahayu; Fikri, Khusnul; Raja, Sutikno (Program Studi Manajemen FEBM UMRAH, 2024)
Human resources must be managed well to increase organizational effectiveness and efficiency, as one of the functions in a company known as human resource management. Human resources are an important element in organizations and companies. Employee performance is very important for company progress. This research aims to determine and analyze the influence of leadership, work motivation and financial compensation on the performance of PT employees. Lutvindo Wijaya Perkasa. The problem formulation in this research is: 1. Does leadership influence employee performance? 2. Does work motivation influence employee performance? 3. Does financial compensation affect employee performance? 4. Do leadership, work motivation and financial compensation influence employee performance? Research Method: This research was conducted using a quantitative approach. The research sample used was 62 respondents using a saturated/census sampling technique. Data analysis used in this research is validity, reliability, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, hypothesis test (t test), simultaneous test (F test) and coefficient of determination test. Hypothesis testing was carried out using the multiple linear regression method with the research results namely that the leadership variable had a positive and significant effect on employee performance, the work motivation variable had a positive and significant effect on employee performance, the financial compensation variable had a positive and significant effect on employee performance, the leadership variable, work motivation and Financial compensation has a simultaneous effect on employee performance. Keywords : leadership, work motivation, financial compensation, employee performance